2018
DOI: 10.15452/nm.2018.09.0011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for urinary incontinence among Istanbul women: a hospital based case-control study

Abstract: Aim: The study aimed to identify risk factors for urinary incontinence in women over 20 years of age in Istanbul. Design: The study was designed as a descriptive, retrospective, case control study. Methods: The study was conducted in a urogynecological unit at a university hospital in Istanbul. In total, 367 incontinent women who visited the urogynecological unit, and 401 continent women who visited outpatient clinics with other gynecological symptoms were included. Data were gathered via face-to-face intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Basak et al 53 stated in their review that the prevalence of UI in Turkish women ranged from 16.4% to 49.7%. The prevalence of UI was reported to be 30.1% in women aged over 40 years by Yagmur and Gul, 54 50.3% in women aged 18–85 years by Demir et al, 55 and 47.8% in women aged over 20 years by Beji et al 56 Consistent with the results of the present study, evidence in the literature as shown above suggests that UI is common among women. Differences in the prevalence between countries and between studies can be attributed to cultural features affecting disease notifications by patients, reluctance or shyness of women and methodological factors affecting investigation of UI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Basak et al 53 stated in their review that the prevalence of UI in Turkish women ranged from 16.4% to 49.7%. The prevalence of UI was reported to be 30.1% in women aged over 40 years by Yagmur and Gul, 54 50.3% in women aged 18–85 years by Demir et al, 55 and 47.8% in women aged over 20 years by Beji et al 56 Consistent with the results of the present study, evidence in the literature as shown above suggests that UI is common among women. Differences in the prevalence between countries and between studies can be attributed to cultural features affecting disease notifications by patients, reluctance or shyness of women and methodological factors affecting investigation of UI.…”
Section: Discussionsupporting
confidence: 91%
“…However, diabetes was also shown to be a risk factor in many other studies 54,55,60,61 which is congruent with the finding of the present study. A study conducted by Beji et al, 56 in Turkey underlined the number of births, obesity and history of UI in one's mother as the most important risk factors of UI. Another study carried out in Turkey showed that giving birth to a high-birth-weight baby, early menarche, menopause, constipation, coffee consumption, lumbar disc herniation, familial history of UI and repeated urinary tract infections are risk factors of all types of UI.…”
Section: F I G U R Ementioning
confidence: 99%